Study of work-hardening behavior of high manganese steel during compression - Wei Pei; Yue Zhang; Shaoguang Yang; Xin Li; Aimin Zhao (Materials Research Express, 2022)
High manganese steels are well used for their excellent hardening properties. In this study, we investigate the mechanical responses of high manganese steel in a compressed condition. During compression deformation, twin crystal is first generated inside some of the grains with orientation advantage, and then all of the grains are twinned. Selective twinning on some grains leads to the formation of textural structures. When the plastic deformation is low, twins appear independently and throughout the grain. After the true strain is more than 0.5, the twins appear as many small parallel short bars. Dislocation density does not increase significantly at the beginning of plastic deformation but increases rapidly while the flow stress no longer increases. Simultaneously, the twinning and the increased density of dislocations increase hardness, with a maximum value of 630 HV at a true strain of 0.6, during plastic deformation.